1983
DOI: 10.1044/jshr.2603.356
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Finger Reaction Time and Voice Reaction Time in Stuttering and Nonstuttering Children and Adults

Abstract: Nine stutterers and nine nonstutterers at each of three age levels (5 years, 9 years, and 18 years and above) responded to the onset of 21 1-kHz tones by depressing the index finger of their preferred hand on a response key. Finger reaction times (FRTs) were measured to the nearest millisecond and compared to the voice reaction times (VRTs) obtained from the same subjects. Increased speed and stability of the finger reaction times were observed as an inverse function of age for both groups. The stutterers, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 0 publications
1
11
1
Order By: Relevance
“…Cross et al [23] observed increased stability of (finger) reaction times as an inverse function of age -examining the individual notification channels confirms this finding as the mean age in the case of simulation is 25.0 years compared to 35.8 years for the real driving study.…”
Section: ) Interpretationsupporting
confidence: 64%
See 1 more Smart Citation
“…Cross et al [23] observed increased stability of (finger) reaction times as an inverse function of age -examining the individual notification channels confirms this finding as the mean age in the case of simulation is 25.0 years compared to 35.8 years for the real driving study.…”
Section: ) Interpretationsupporting
confidence: 64%
“…For definitive confirmation it would be essential to conduct further studies with test persons in a broader range of age, e. g., age group 18 to 65 [21]. Initial evaluations with respect to age have been presented by Riener [24] for the trace-driven experiment -the order of variance (364.94ms for the group of persons aged 25 years or below, 337.37ms for the group older than 25 years) follows the findings presented by Cross and Luper [23], and are confirmed within this work.…”
Section: ) Interpretationmentioning
confidence: 88%
“…The authors also commented on the observation that the instruction on how to respond to pitch shift stimuli had a significant effect on response latency and magnitude. The observation that the instructions affected response characteristics is not unusual considering that studies of voluntary voice reaction times (Izdebski and Shipp, 1978;Cross and Luper, 1983;Shipp et al, 1984;Bakker and Brutten, 1989;Watson, 1994) and vocal shadowing studies (Leonard and Ringel, 1979;Horii, 1984;Leonard et al, 1988;Bailly, 2003;Shockley et al, 2004;Peschke et al, 2009) lead to responses with latencies that are similar to the responses reported by Hain et al (2000).…”
Section: Introductionmentioning
confidence: 58%
“…In the vocal reaction time experiments, subjects typically initiate vocalization as fast as possible following a stimulus such as an auditory cue. Results of these experiments reveal voice reaction times in the range of 150-250 ms (Izdebski and Shipp, 1978;Cross and Luper, 1983;Shipp et al, 1984;Bakker and Brutten, 1989;Watson, 1994). These studies indicate that people are capable of initiating or volitionally changing their voice (F0 or amplitude) within about 200 ms of a stimulus.…”
Section: Discussionmentioning
confidence: 77%
“…Research is being carried out to compare the overall capacity of the cen tral nervous system of stuttering and of non stuttering children (voice initiation time, voice termination time, finger reaction time [12,14], Peripheral Speech Production. Research is also being carried out in the field of peripheral speech production [15][16][17][18][19].…”
Section: Current Research Situationmentioning
confidence: 99%